Impact of sedation, body position change and continuous positive airway pressure on distribution of ventilation in healthy foals - Sacks, Muriel; Raidal, Sharanne; Catanchin, Chee Sum Melanie; Hosgood, Giselle; Mosing, Martina (Frontiers in Veterinary Science, 2023)
Background: This study aimed to compare the distribution of ventilation measured by electrical impedance tomography (EIT), in foals under varying clinical conditions of sedation, postural changes, and continuous positive airway pressure (CPAP). To support the interpretation of EIT variables, specific spirometry data and F-shunt calculation were also assessed. Materials and Methods: Six healthy Thoroughbred foals were recruited for this sequential experimental study. EIT and spirometry data was recorded: 1) before and after diazepam-sedation, 2) after moving from standing to right lateral recumbency, 3) in dorsal recumbency during no CPAP (CPAP0) and increasing levels of CPAP of 4, 7 and 10 cmH2O (CPAP4, 7, 10, respectively). Ventral to dorsal (COVVD) and right to left (COVRL) center of ventilation, silent spaces, tidal impedance variation, regional ventilation distribution variables and right to left lung ventilation ratio (R:L) were extracted. Minute ventilation was calculated from tidal volume (VT) and respiratory rate. F-Shunt was calculated from results of arterial blood gas analysis. Statistical analysis was performed using linear mixed effects models (significance determined at p < 0.05). Results: 1) Respiratory rate was lower after sedation (p = 0.0004). 2) In right lateral recumbency (compared to standing), the COVVD (p = 0.0012), COVRL (p = 0.0057), left centro-dorsal (p = 0.0071) and dorsal (p < 0.0001) regional ventilation were higher, while the right ventral (p = 0.0016) and dorsal (p = 0.0145) regional ventilation, and R:L (p = 0.0017) were lower. 3) Data of two foals for CPAP10 was excluded from statistical analysis due to prolonged apnea. Stepwise increase of CPAP led to increases of COVVD (p = 0.0028) and VT (p = 0.0011). A reduction of respiratory rate was detected with increasing CPAP levels (p < 0.0001). Conclusions: 1) In healthy foals, diazepam administration did not alter distribution of ventilation or minute ventilation, 2) lateral recumbency results in collapse of dependent areas of the lung and 3) the use of CPAP in dorsal recumbency at increasing pressures improves ventilation in dependent regions, suggesting improvement of ventilation-perfusion mismatch.